IMPLEMENTASI TEORI BELAJAR SERTA PERANAN GURU PAI DALAM MENINGKATKAN MOTIVASI BELAJAR GENERASI Z DI ERA DIGITAL - Rahma Ihda Fatimah Azzahro; Abdan Syakuro; Lathifatus Sa Diyyah; Nurlaila Ana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The advancement of digital technology has brought significant transformation to students' learning patterns, particularly for Generation Z, whose growth and development occur in an environment strongly influenced by the use of information technology. The characteristics of Generation Z, who are very familiar with the internet, social media platforms, and various digital applications, demand strategic adjustments in learning approaches to ensure an effective educational process and to optimally enhance learning motivation. This study aims to comprehensively examine the learning characteristics of Generation Z in the digital era, identify learning theories that are relevant to these characteristics, analyze the role of Islamic Education teachers in increasing learning motivation, and explain the implementation of learning theories that suit the needs of today's students. This study uses a literature review method with a descriptive qualitative approach. Data collection was carried out through various secondary sources in the form of scientific journals, reference books, academic articles, as well as previous research findings that were relevant to the research topic. The results of the study show that Generation Z has learning characteristics that are interactive, visual, quick in accessing information, and tend to expect technology-based learning. Constructivism and connectivism theories are considered highly relevant to be implemented in the context of Generation Z learning. PAI teachers play the role of motivator, role model, and murabbi in the learning process. The implementation of learning theories supported by the use of digital technology has been proven to increase motivation, engagement, and learning effectiveness for Generation Z in the contemporary digital era.